A mechanistic approach to blood flow occlusion - Loenneke, J. P.; Wilson, G. J.; Wilson, J. M. (International Journal of Sports Medicine, 2010)
Low-Intensity occlusion training provides a unique beneficial training mode for promoting muscle hypertrophy. Training at intensities as low as 20% 1RM with moderate vascular occlusion results in muscle hypertrophy in as little as three weeks. The primary mechanisms by which occlusion training is thought to stimulate growth include, metabolic accumulation, which stimulates a subsequent increase in anabolic growth factors, fast-twitch fiber recruitment (FT), and increased protein synthesis through the mammalian target of rapamycin (mTOR) pathway. Heat shock proteins, Nitric oxide synthase-1 (NOS-1) and Myostatin have also been shown to be affected by an occlusion stimulus. In conclusion, low-intensity occlusion training appears to work through a variety of mechanisms. The research behind these mechanisms is incomplete thus far, and requires further examination, primarily to identify the actual metabolite responsible for the increase in GH with occlusion, and determine which mechanisms are associated to a greater degree with the hypertrophic/anti-catabolic changes seen with blood flow restriction.